The Socio-Cultural System of Banjar Migrants' Marriage in Tulungagung from 1980 to 2018: Sistem Sosial Budaya Perkawinan Masyarakat Migran Banjar di Tulungagung Tahun 1980-2018 - Tri Sakti Tunggal Dewi; bambang soepeno; sugiyanto sugiyanto; kayan swastika (JURNAL HISTORICA, 2019)
In 1920, many Banjar people migrated to Tulungagung. Banjar community gradually grew more and more to the end of the interaction with the indigenous peoples of Tulungagung the majority of Javanese people. Therefore, from the interaction, in the year 1980 Banjar Migrant society is doing marriage with the people of Tulungagung who are aiming to establish their lives. At first the implementation of the marriage still follows the customs of the Banjar people, so it has not seen the function of marriage between Banjar and Java. Therefore, the existence of the marriage has emerged cultural influences and occurred accultutation. In the year 1987 when there began to be many who did the marriage between the two tribes, began to see a change of function in the marriage by looking at the customary clothing used and in the provision of Mahar. Then there is also a function of marriage that appears, judging by the use of customary marriage used based on the customary origin of the bride candidate. So that in the year 1991 to 2018 Acculturation is seen from the customary marriage that is used based on the origin of the bride candidate. Keywords: Banjar Community, Banjar and Javanese Marriages, Tulungagung.